Fighting over words language and civil law cases - Shuy, Roger W. (New York : Oxford University Press, 2008)
Civil law cases offer many examples of language being at the center of human conflict. Contract disputes, truth in advertising, product warning labels, plagiarism, etc. often boil down to a matter of language - its meaning and usage. This book analyzes 18 civil cases in which language framed the battleground.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- Language; Law -- Interpretation and construction; Civil law -- Cases